Performance evaluation of a solar ORC system using evacuated flat plate photovoltaic-thermal collector as an evaporator - Izaz Ahmad Qureshi (00000203669); Dr. Adeel Waqas (USPCAS-E, NUST, Islamabad, 2020)
TH-216
Keywords: MS-ESE Thesis MS Thesis